(untitled) (Cardiovascular Journal, 2017)
Background: High preoperative BNP levels can be a marker of higher risk for coronary artery bypass grafting. We investigated the predictive value of serum NT-proBNP levels undergoing coronary artery bypass grafting for the need for inotropic support. Methods: In this prospective study, preoperative serum NT-proBNP levels were obtained in 51 patients [80.4% (n=42) were males and 19.6% (n=9) were females] undergoing isolated coronary artery bypass grafting. The study patients were divided into three groups depending on NT-proBNP levels as low NT-proBNP (<100 pg/ml, Group-1, 29.4%, n=15) group, moderately high NT-proBNP (NT-proBNP <500 pg/mL and >100 pg/mL, Group-2, 29.4%, n=15) group, and high NT-proBNP (>500 pg/mL, Group-3, 41.2%, n=21) group. Results: At postoperative day 0, the mean adrenalin, dopamine, dobutamine, and noradrenalin consumptions were 0.1±0.7 microgram/kg/min, 0.08±0.56 microgram/kg/min, 2.1±3.01 microgram/ kilogram/min, and 1.35±3.45 microgram/kg/min, respectively. There were no statistically significant differences between the groups in terms of the use of adrenalin (p=0.50, p>0.05), dopamine (p=0.31 p>0.05), dobutamine (p=0.59 p>0.05), and noradrenalin (p=0.24 p>0.05) at postoperative day 0. The doses of inotropic agents used at postoperative days 1 and 2 did not show significant differences between the groups for the three inotropic agents. Conclusion: Preoperative serum NT-proBNP levels in patients undergoing coronary artery bypass grafting are not associated with the need for inotropic support in the postoperative period. Cardiovasc. j. 2017; 9(2): 90-96